Electrical, Magnetic and Dielectric Properties of Cobalt-Doped Barium Hexaferrite BaFe12−xCoxO19 (x = 0.0, 0.05, 0.1 and 0.2) Ceramic Prepared via a Chemical Route - Kumar A.; Verma M.K.; Singh S.; Das T.; Singh L.; Mandal K.D. (My University, 2025)
BaFe12−x CoxO19 (BHFC) hexaferrites with compositions (x = 0.0, 0.05, 0.1 and 0.2) were successfully synthesized by a chemical route at 1150°C for 12 h. Single-phase formation for BaFe12−x CoxO19 (x = 0.0, 0.05, 0.1) were confirmed by x-ray diffraction (XRD) patterns. However, a small amount of secondary phase of Fe2O3 was found in the case of high-percentage substitution of Co (x = 0.2). Le Bail analysis and transmission electron microscopy (TEM) analysis confirmed the existence of a hexagonal structure in the BHFC ceramics for all the synthesized compositions with lattice parameters a = b = 5.88603 Å, c = 23.18299 Å and space group P63/mmc. The average crystallite sizes were found to be 41.48 nm, 39.02 nm, 35.99 nm and 33.56 nm, respectively, using the Debye–Scherer equation. The Fourier transform infrared (FTIR) spectrum was recorded in the frequency range of 5000–400 cm−1 at room temperature to explain the presence of M–O such as Fe–O, Ba–O and Co–O bonds and Fe–O–Fe (M–O–M) bonds in BHFC ferrites. The presence of M–O and M–O–M bonds was also confirmed by the phase formation of hexagonal ferrites. The hexagonal plate-like structure was observed using scanning electron microscopy (SEM). BHFC ceramics displayed average grain size 0.50 μm, 0.84 μm and 1.0 μm for the compositions (x = 0.0, 0.05 and 0.1), respectively. Magnetic, dielectric and AC conductivity measurements were carried out using a vibrating-sample magnetometer (VSM) and impedance analyzer, respectively. The saturation magnetization (Ms) of the BHFC ceramic observed by magnetic measurements was lower than pure barium hexaferrite materials. The value of the dielectric constant (ε) for the BHFC ceramic was found to be 2.3 × 103 at 100 Hz. © 2020, The Minerals, Metals & Materials Society.